THE IBAN'S BELIEF TOWARDS THE PUA KUMBU'S MOTIF - Alexander, Chelum; Anna, Durin; Connie Lim, Keh Nie; Asrul Asshadi, Mohamad Morni; Noria anak, Tugang; Qistina Donna, Lee Abdullah (UNIMAS Publisher, 2017)
The Iban, the largest ethnic group in Sarawak, are traditionally riverine communities whose cultural identity is deeply rooted in subsistence agriculture, longhouse living, and a strong connection to rivers and forests. Despite widespread conversion to Christianity, traditional animistic beliefs continue to influence Iban cosmology, which emphasizes the interaction between humans (mensia) and the spiritual realm (antu or petara). Central to this worldview is Pua Kumbu, a traditional Iban textile that embodies cultural values, spiritual beliefs, and social hierarchy through its motifs. These motifs symbolize attributes such as bravery, protection, healing, and prosperity, and are classified into high- and low-status categories. High-status motifs, often inspired through dreams and associated with powerful beings or deities, require spiritual preparedness and ritual observance, while low-status motifs are more commonly woven. Pua Kumbu plays a vital role in Iban ceremonial life, including weddings, agricultural rituals, festivals, and funerals, serving protective, symbolic, and spiritual functions. Ritual practices, such as “feeding” dangerous motifs and observing taboos in weaving, reflect enduring animistic beliefs that attribute agency and power to textile designs. Although modernization has altered some traditional practices, Pua Kumbu remains a significant cultural artifact that reflects the continuity of Iban cosmology, values, and identity within contemporary society.